The Urgency Of Implementing Sharia Accounting In Sharia Financial Institutions In The Indonesian Context: Bibliometric Analysis - Aprielle Ego Pasha; Sugianto Sugianto (Universitas Veteran Bangun Nusantara, 2024)
Sharia accounting has an important role in a sharia bank to help record financial reports. through recording financial reports will help produce quality, ideal and transparent financial report information. This research aims to determine the mapping of sharia accounting research on Sharia Financial Institutions in Indonesia from 2013 to 2023 and find out the importance of implementing sharia accounting in Sharia Financial Institutions. The approach used is quantitative with bibliometric analysis methods. The data source used is secondary data from the Garuda portal (Garba Reference Digital) and analyzed using VOSviewer software. The research results show that the number of scientific article publications on the application of sharia accounting in sharia financial institutions from 2001 to 2023 was 107 articles divided into 8 clusters and 58 topics.